Pengaruh Evaluasi Kerja, Pelatihan Dan Pengawasan Terhadap Peningkatan Mutu Kinerja Karyawan Pt.Nutrihub Medan - Moris Sarullo Panjaitan; Yesshy Vembryka Siahaan; Dhita Adriani Rangkuti; Selpya Ramawati Zega; Bena Br Ginting (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research was conducted to determine the effect of job evaluation, training and supervision on the quality of employee performance of PT. Nutrihub Medan. The purpose of this research is to find out and analyze how work evaluations are given to employees, how training is given to employees, how supervision is given to employees, and to find out how the e ffect of work evaluation, training and supervision simultaneously on the quality of employees performance of PT. Nutrihub Medan. This research uses quantitative methods with descriptive research types. Sampling was carried out using a saturated sampling technique, with a total of 76 respondents. The calculation process is processed with the help of (SPSS) ver 24 for windows. The data analysis technique used is multiple linear regression analysis. Based on the results of this study, simultaneously the variables of work evaluation, training, and supervision have a significant effect on employee performance by 54.2%. The conclusion of this study is that work evaluation, training and supervision have a positive and significant effect on the quality of employee performance of PT. Nutrihub Medan. Keywords: Job Evaluation, Training, Supervision